Criteria system to assess the performance of hi-tech business incubators - Tung, Nguyen Thanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The establishment and development of hi-tech business incubators have been received due attention of the Party and State for many years with a view to creating favorable conditions for the formation and development of high-tech enterprises, thus contributing to fostering the commercialization of research results and the application of high technologies in production. The Law on High Technology (2008) stipulated functions, conditions and measures to promote and support the development of high-tech business incubators. The strategy for science and technology (S&T) development for 2011-2020 also set a target of establishing 30 and 60 high-tech business incubators by 2015 and 20201, respectively. So far, there have been various high-tech business incubators with more than 5 years of operation. Furthermore, many organizations and local governments are presently promoting the establishment of business incubation facilities or conducting preparatory studies to establish high-tech business incubators. In order to facilitate the efficient operation of newly established incubators and effective application of the State’s incentive policies in this respect, it is indispensable for management agencies to conduct an assessment on the actual performance of existing high-tech business incubators to understand of how it look like? To what extent the expected results have been obtained and the set objectives have been achieved so far? What are their impacts on socio-economic, scientific and technological development? Whether or not it has met the requirements of the State on the development of high-tech business incubation? This assessment exercise is to not only show the achievements, but also identify causes of success and possible constraints. The purpose of this paper is to create an analytical framework (approach) with scientific and practical basis, and from there to propose a set of criteria to assess the performance of high-tech business incubators. Code: 14042901